La difícil aplicación de la Doctrina Social de la Iglesia en España. La gestación de la Escuela Social de Zaragoza (1907-1929) / The Difficult Application of the Social Doctrine of the Church in Spain. The Creation of the Zaragoza Social School (1907-1929) - Fernando Crovetto (Studia et Documenta, 2025)
The Social School of Zaragoza was the practical manifestation of the social concern of a group of Aragonese Catholics who sought to raise social concern among the Spaniards of their time. The school was a pioneer in the Iberian Peninsula and was concerned with spreading the social doctrine of the Church through study and the dissemination of the teachings of the Roman pontiffs. Josemaría Escrivá met some of its members when he was studying law at the University of Zaragoza. This article aims to present the theoretical foundations of the group and describe some of its initiatives as a formative context for the founder of Opus Dei.